UPAYA MENINGKATKAN HASIL BELAJAR PEMBELAJARAN PASSING BAWAH BOLA VOLY MELALUI METODE BERMAIN SISWA KELAS V - Muh. Eko Tirto Noviyantoro (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This research aims to improve learning outcomes under passing on volleyball game using the play method. This research using the Classroom Action Research (PTK) approach. The subject of this research  of class V of elementary school at SDN Pandan 1 Omben. This research was conducted with six meetings consisting of two cycle, every cycle 3 times meeting. The first cycle that is realized through action according to the plan and learning method, the result is 74% of students graduate. In the second cycle which is realized through reflection action results from cycle 1, the result is the average value of students in underpass learning increases to 92% of students graduating. Based on the results of the study can be concluded that passing under learning using the play method can improve student learning outcomes in class V at SDN Pandan 1 Omben